Tindakan Menjaga Kebersihan Rongga Mulut Mahasiswa Kedokteran Gigi Tingkat Akhir - Wistarin, Felicia Fransisca Maggie Christi; Albert (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Ignoring dental and oral hygiene can cause a variety of illnesses such as tooth decay and periodontitis. One of the symptoms caused by tooth decay is a change in tooth color. Periodontitis is characterized by bleeding, discoloration, viscosity, and edema of the gums. Periodontitis is characterized by the presence of periodontal pockets, recession, or both. Bad breath can be part of periodontitis. Object : This study was conducted to obtain descriptive data on individual attitudes and behaviours for maintaining dental and oral health in preclinical students in their final year. Method: The target of this activity is the final stage preclinical student of DKI Jakarta School of Dentistry. The revised Indonesian Hiroshima University-Dental Behavioural Inventory (HU-DBI) questionnaire was distributed to 103 respondents. Data processing uses the sum of the question values and percentages. Results: The data collected show that female respondents are not always good at keeping their teeth clean. Toothpaste is common, but dental floss and mouthwash are not used on a daily basis. The incidence of periodontitis does not occur in most senior students. Conclusion: Female respondents are more willing to maintain dental and oral health than male respondents. Male respondents have better dental and oral hygiene practices than female respondents. The actions of male respondents do not perform correctly for all questions. The use of dental floss and mouthwash achieved good results among female respondents.